Sandra Cisneros - Castellano, Alcario:::creator::::::::::::
Video and transcripts of Sandra Cisneros as a guest speaker (5:57). She introduces her childhood in Chicago, the influences for her writing; a college English writing course awakened the concept of writing about her "house", the topics of privilege, belonging and class - all contributed to the creation of The House on Mango Street. Ciscneros starts answering audience questions. (48: 32-1:25:04). The video ends with Sandra Cisneros signing books before leaving the event (1:25:04-1:49:06).